The concept and principles of local self-government in the Republic of Belarus and Republic of Kazakhstan: the value of the content, the comparative analysis - Terenik, Olga (Journal of the Belarusian State University. Law, 2019)
In this paper the author investigated the concept and principles of local self-government in the Republic of Belarus and Kazakhstan: the value of the content, the comparative analysis. Based on analysts scientific papers in this field, the author proves the relevance of local government at the present stage. The paper deals with the legal framework of local government in the Republic of Belarus and Kazakhstan, a comparison of the relevant legislation is the content of the European Charter of Local Self-Government. By analyzing and comparing the principles of local self-government in the legislation of the Republic of Belarus and Kazakhstan, the author makes some suggestions of making amendments to the legislation in the States concerned in the field of local self-government.
Keywords: state structure; local government; local self-government; principles of local self-government